Necessary lies eaudiobook A novel. - Chamberlain, Diane (Necessary Lies, 2013)
Bestselling author Diane Chamberlain delivers a breakout book about a small southern town fifty years ago, and the darkest—and most hopeful—places in the human heart After losing her parents, fifteen-year-old Ivy Hart is left to care for her grandmother, older sister and nephew as tenants on a small tobacco farm. As she struggles with her grandmother's aging, her sister's mental illness and her own epilepsy, she realizes they might need more than she can give. When Jane Forrester takes a position as Grace County's newest social worker, she doesn't realize just how much her help is needed. She quickly becomes emotionally invested in her clients' lives, causing tension with her boss and her new husband. But as Jane is drawn in by the Hart women, she begins to discover the secrets of the small farm—secrets much darker than she would have guessed. Soon, she must decide whether to take drastic action to help them, or risk losing the battle against everything she believes is wrong. Set in rural Grace County, North Carolina in a time of state-mandated sterilizations and racial tension, Necessary Lies tells the story of these two young women, seemingly worlds apart, but both haunted by tragedy. Jane and Ivy are thrown together and must ask themselves: how can you know what you believe is right, when everyone is telling you it's wrong?